The role of aldosterone and ideal cardiovascular health in incident diabetes: The Jackson Heart Study - Veena Kesireddy; Bjorn Kluwe; Neal Pohlman; Songzhu Zhao; Yubo Tan; David Kline; Guy Brock; James B. Odei; Valery S. Effoe; Justin B. Echouffo-Tcheugui; Rita R. Kalyani; Mario Sims; et al. (Elsevier, 2023)
Background: Greater attainment of ideal cardiovascular health (ICH) and lower serum aldosterone are associated with lower diabetes risk. Higher levels of ICH are associated with lower aldosterone. The mediational role of aldosterone in the association of ICH with incident diabetes remains unexplored. Thus, we examined the mediational role of aldosterone in the association of 5 ICH components (smoking, diet, physical activity, body mass index [BMI], and cholesterol) with incident diabetes. Additionally, we investigated the mediational role of glucose and blood pressure (BP) in the association of aldosterone with incident diabetes in an African American (AA) cohort. Methods: We conducted a prospective cohort analysis among AA adults, aged 21-94 years, in the Jackson Heart Study. Data on ICH, aldosterone, and cardiometabolic risk factors were collected at exam 1 (2000-2004). Diabetes (fasting glucose ≥ 126 mg/dL, physician diagnosis, use of diabetes drugs, or glycated hemoglobin ≥ 6.5%) was assessed at exams 1 through 3 (2009-2012). ICH metrics were defined by American Heart Association 2020 goals for smoking, dietary intake, physical activity, BMI, total cholesterol, BP and glucose. The number of ICH metrics attained at exam 1, excluding BP and fasting glucose, were summed (0-2, vs. 3+). R Package Mediation was used to examine: 1) The mediational role of aldosterone in the association of ICH with incident diabetes; and 2) the mediational role of BP and glucose in the association of aldosterone with incident diabetes. Results: Among 2,791 participants (mean age: 53±12, 65% female) over a median of 7.5 years, there were 497 incident diabetes cases. Risk of incident diabetes was 37% (HR: 0.63, 95%CI: 0.47, 0.84) lower in 3+ ICH category compared to 0-2 ICH category. Aldosterone mediated 6.98% (95% CI: 1.8%, 18.0%) of the direct effect of ICH on incident diabetes. A 1-unit increase in log-aldosterone was associated with a 44% higher risk of diabetes (HR 1.44, 95%CI 1.25-1.64). BP and glucose mediated 16.3% (95% CI: 7.0%, 31.0%) and 19.7% (95% CI: 6.5%, 34.0%) of the association of aldosterone with incident diabetes, respectively. Conclusion: Aldosterone is a mediator of the association of ICH with incident diabetes, whereas BP and glucose are mediators of the association of aldosterone with incident diabetes, emphasizing the importance of the renin-angiotensin-aldosterone system and ICH in lowering risk of diabetes in AA populations.